AFLATOXIN CONTAMINATION AND NUTRITIONAL EVALUATION OF DRIED JUVENILE FISH (Clarias gariepinus) SOLD IN IBADAN METROPOLITAN MARKETS - Adebami, Gboyega E.; Esan, Olasumbo H.; Adebayo-Tayo, Bukola C.; Maloma, Mojisola R. (FUDMA Journal of Sciences, 2024)
The contamination of food due to the occurrence of mycotoxigenic fungi is a public health concern. Therefore, fungi and aflatoxin contamination of smoked-dried juvenile fish (SDJF) (Clarias gariepinus) were investigated. The samples were purchased from three major markets in Ibadan. The total fungal count ranged from 1.0 x 103 to 12.0 x 103 CFU/g. Thirty-two fungi were isolated, including Penicillium sp., Rhizopus sp., Alternaria sp., Aspergillus flavus, Aspergillus niger, and Aspergillus ochraceus. A. niger had the highest frequency of occurrence (38%), while A. ochraceus (3%) had the lowest. All the samples were contaminated with aflatoxin. The total aflatoxin content ranged from 0.237 to 1.995 ppb. Of the 11 Aspergillus strains obtained from the samples, 5 were aflatoxigenic, while 6 were not. 85 and 94% of the mycobiota were xerophilic and halophilic. The percentage moisture content, crude protein, crude fat, and ash content in the samples ranged from 12.99–17.82%, 68.72–77.62%, 0.49–6.00%, and 6.97–12.24%. Phosphorus and potassium concentrations of the SDJF samples ranged from 388.2–509.6 mg/100g and 1113.8–1517.0 mg/100g, while lead and cadmium were not detected in the samples. Though the level of aflatoxin contamination in this study was within the maximum limit permitted (20 ppb), proper attention is needed for adequate preservation before sales and consumption.
Keywords: Aflatoxin; Aspergillus spp; Clarias gariepinus; Dried juvenile-fish; Mycotoxigenic fungi